Femtosecond formation dynamics of the spin Seebeck effect revealed by terahertz spectroscopy - Tom S. Seifert (Nature Portfolio, 2018)
Probing spin pumping in the terahertz regime allows one to reveal its initial elementary steps. Here, the authors show that the formation of the spin Seebeck current in YIG/Pt critically relies on hot thermalized metal electrons because they impinge on the metal-insulator interface with maximum noise.